Hubungan Sikap Kesehatan Gigi dan Mulut Penderita Terhadap Kepatuhan dalam Menjalani Perawatan Berulang - Rizkina Hendani; Edhie Arif Prasetyo; Galih Sampoerno (Conservative Dentistry Journal, 2017)
Background: Caries is the world's number one chronic disease and the prevalence increases in modern times. But most people ignore it and choice dental care only when it feels pain. It will worsen the condition of the tooth until require multivisit treatments. The number of visits required for multivisit treatments results incomplete treatment due to patient’s non-obedience. One of the factors that affect obedience is attitude. One's attitude towards something will determine someone's behavior towards the same thing. Purpose: To determine the relationship of patient’s dental and oral health attitude towards patient’s obedience during multivisit treatment. Method: Analytical observational research with cross-sectional study conducted on 30 patients who came to RSGMP UPF Conservative Dentistry FKG UNAIR Surabaya period September-November 2011. The data about the attitude is obtained from questionnaire, while collecting cards of patient’s status and direct interviews of the operators conducted to obtain data about patient’s obedience. Result: Based on the results of Spearman Correlation with α=0,05 obtained p-value=0,364 (p>0,05). It suggests that there is no significant relationship between patient’s dental and oral health attitude towards patient’s obedience during multivisit treatment. In addition, test results of the relationship between unexamined variables with obedience obtained p-value=0,010 (motivation), p=0,017 (desire), p=0,004 (perception), and p=0,009 (financing). This suggests that there is a significant relationship between motivation, desires, perceptions, and financing with obedience. Conclusion: There is no relationship between patient’s dental and oral health attitude towards patient’s obedience during multivisit treatment. However, other factors found associated, namely motivation, desires, perceptions, and financing.